Gender equality discourse in islamic online media in social and contemporary history, 2000-2021 - Yuliantri, Rhoma Dwi Aria; Aman, Aman; Akalili, Awanis (Informasi, 2023)
The article examine gender discourse channelled through Suara Aisyiyah magazine, part of Aisiyah, woman organization, with a gender perspective discoursed through online media. However, representations of gender discourse vary in different spaces and times, as well as different agents and contexts. Likewise with ways to channel ideas about gender that are part of the organization's vision. To capture the transformation of gender discourse with online media, this study uses a historical approach with discourse analysis. Discourse analysis method to describe text and context will be used in data analysis. The periodization which is the starting point of this research is 2000-2021 (contemporary period). The digital platform is used to more broadly discuss the progressive Islamic identity that is carried by Suara "˜Aisyiyah, in that period. As we understand, online media has carried many identities, thus allowing "crossing" and "collision". The various discourses raised by the Suara "˜Aisyiyah print newspaper clearly show the vision of the "˜Aisyiyah and Muhammadiyah organizations, such as the position of women in politics and women's access to health and nutrition. Through preaching on social media, the spirit of equality was built by "˜Aisyiyah in all walks of life, such as by promoting the Elimination of Domestic Violence.